Processed Meat and Risk of Renal Cell and Bladder Cancers. (3rd April 2018) - Rosato, Valentina; Negri, Eva; Serraino, Diego; Montella, Maurizio; Libra, Massimo; Lagiou, Pagona; Facchini, Gaetano; Ferraroni, Monica; Decarli, Adriano; La Vecchia, Carlo
ABSTRACT: We assessed the association of processed meat intake with the risk of renal cell carcinoma (RCC) and bladder cancer. We used data from two Italian hospital-based case-control studies, including 1, 115 RCC cases and 2, 582 controls, and 1, 417 bladder cancer cases and 1, 732 controls. We calculated odds ratios (ORs) and 95% confidence intervals (CIs) with unconditional logistic regression models, adjusted for major confounders. The median consumption of processed meat in cases and controls was around 2 portions/week (50 g/portion). The ORs for a daily 10 g increment of processed meat was 0.89 (95% CI 0.84–0.94) for RCC and 1.00 (95% CI 0.94–1.06) for bladder cancer. The OR for the highest vs. the lowest consumption was 0.80 (95% CI 0.66–0.96) for RCC and 0.98 (95% CI 0.80–1.21) for bladder cancer. The ORs were consistent in strata of various covariates. For bladder cancer, however, a significant 23% excess risk was found in women (95% CI 1.03–1.47) for a daily increase of 10 g, significantly heterogeneous from the risk recorded in men (OR 0.96, 95% CI 0.90–1.02). The inconsistent results between men and women and the absence of association in both sexes combined indicate that the apparent association between processed meat and bladder cancer in women is unlikely to be causal.